Electrode area analysis of EEG signals received from schizophrenic individuals - AKGÜN, ÖMER (My University, 2022)
It is very difficult to distinguish between healthy and schizophrenic individuals based on raw data. However, with the analyzes made, the separation of healthy and sick individuals from each other has become quite evident. In the study, EEG signals were obtained by means of electrodes from the anterior region, middle and posterior regions of the brain, and analyzed according to their positions. Apart from the time-amplitude graph, PSD and STFT analyzes have also performed the analyzes and the results were compared. As a result of this study, the results of PSD analysis are quite successful in distinguishing between healthy and schizophrenic individuals. In this sense, this method includes features that can be used by physicians for diagnostic purposes. In addition, the analysis results are compatible with each other and the results are meaningful. In particular, the results of PSD analyses give very distinctive results that can be used for diagnosis. In addition, the results of the analyzes made with the STFT method are also compatible with the PSD analyses, where healthy individuals have a trend of around 10 Hz, and individuals diagnosed with schizophrenia have a trend of up to 20 Hz.
Keywords: EEG; Schizophrenia; STFT; PSD Welch method